Previously reported approach now used for temporomandibular joint replacement (2020)
Over time, different techniques have been described to obtain broad access to the temporomandibular joint (TMJ), in order to allow good visibility, minimizing post-operative complications at the same time. Most of these techniques have been very useful to perform joint replacement using custom made prostheses, varying in its extension, aesthetics and functional results. The aim of this study was to present the authors' experience using the Blair approach modified by Fernández in 2015, to replace failed TMJ prostheses, when distortion of the surgical reference points has occurred.